Strengthening dialogue : UN experience with small farmer organizations and indigenous peoples - McKeon, Nora (NGLS GenevaCH, 2009)
Argues that it is crucial, urgent and feasible to enhance the United Nations system's engagement with people's movements in relation to the UN's overarching development and human rights agenda.